(untitled) (International Journal of Ayurveda and Pharma Research, 2023)
Vibandha/Baddapureesha means Sanga or obstruction for the passage of stool, and this condition can be due to the functional or structural. Vibandha (constipation) has been described in numerous places. In conditions like Udavarta, it manifests as a separate entity, and in diseases like Kasa and Shwasa, it plays a significant role in the occurrence of Samprapti. Vibandha as a separate entity has not been described by any major text in Ayurveda. Its Lakshana includes voiding of small quantity of stool with difficulty or voiding a large quantity of watery stool with sound and pain. Current era due to lifestyle, fast and stressful life, humans are frequently led towards irregular and bad habits of Ahara, Vihara and Vegadharana leading to several problems like Vibandha, Ajirna, Sthoulya etc. Vibandha not only caused because Pureeshavahasrotho Dusti it can also be caused because of Apanavata Vaigunya along with Agnimandya. As Agni is responsible for the formation of Pakwa Mala, Agnimandya is considered as main cause for Vibandha. Hence Agni plays a significant role in Vibandha.